An Examination of Depressive Symptoms in Adolescents: The Relationship of Personality Traits and Perceived Social Support - Sami, Abdul Hanan; Naveeda, Naveeda (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2021)
Present study aimed at investigating the association between personality traits, perceived social support and depressive symptoms in adolescents. Through convenient sampling, total 302 students (110 males and 192 females) were recruited from different universities of Rawalpindi and Islamabad. The age range of sample was 18-25 years. In present study, The Big Five Inventory- Short Version (BFI-S) (Gerlitz & Schupp, 2005), The Multidimensional Scale of Perceived Social Support (MSPSS) (Zimet et al., 1988), and Depression, Anxiety and Stress Scale (DASS-21) (Lovibond & Lovibond, 1995) were used to access personality traits, perceived social support and depressive symptoms. Findings of the present study showed a significant positive relationship between neuroticism and depressive symptoms. However, extraversion, conscientiousness and perceived social support showed significant negative association with depressive symptoms. According to regression analysis, neuroticism is a positive while, perceived social support is significant negative predictor of depressive symptoms in young adolescents. Furthermore, findings of present study may assist in identifying the personality traits at risk of experiencing depression.